The regression calculus of economic convergence and the contribution of the institutional factor - Aurel Iancu; Eugen Stefan Pecican; Dan Olteanu (Romanian Academy, National Institute for Economic Research, 2010)
This working paper aims to stress the role of the institutional capital and its components, as primary factors, in economic results at the national level, using adequate measurement indicators and econometric models. For this purpose, we analysed the following aspects: the definition of institutional capital and its components with regard to its operationalisation; the numerical expression of the institutional capital and its components by indicators, as well as the description of their content; the confirmation of the significant influence of the institutional capital on economic results. For applying several variants of econometric models including two or more variables to two samples (EU countries and world countries), special attention is paid to matters concerning the checking of the assumption about factor independence, multicolinearity and the attenuation of the consequences of this characteristic. Among the components of the institutional capital, the highest influence on the economic results indicated by the selected samples is exerted by the macroeconomic environment, and, within this environment, by the country rating and the macroeconomic stability.
Keywords: C5; C8; O43; O47; 330; institutional capital; public institutions; macroeconomic environment; indicators; econometric models; regression analysis; testing multicolinearity; production function.